Quando a batida da tranca embala o romance: notas sobre relações afetivo-amorosas no contexto penitenciário da Colônia Penal Feminina do Recife/Bom Pastor - Araújo, Nathielly Darcy Ribeiro (2017)
This work emerges from the attempt to understand the dynamics of the affectionate/amorous relationships in the lives of female prisoners at the Female Penal Colony of Bom Pastor, Recife, Pernambuco. The main objective was to understand through the dynamic of visits (with focus on intimacy) how these relationships are organized in the context of the institutionalization to which these women have been subjected. In this way, by ethnographic inquiry and having, as a base, a bibliography by authors who contemplate themes related to the body, violence, total institutions and intimate relationships, there was traced, by way of interviews performed with female prisoners receiving intimate visits at the Penal Colony, the dynamic of affectionate relationships alongside the trajectories of their lives. In this way, in the face of the mechanisms of power present within the prison context, the study was able to analyze how the internees develop their relationships within a context where they are controlled and monitored. The importance of the work resides in the contemplation of intimacy within that specific dynamic where rules are imposed and privileges withdrawn.